Effective treatment for prevention of post-operative adhesion after strabismus surgery in experimental rabbit model: 0.5 % tranilast ophthalmic solution. Issue 1 (December 2016) - Choi, Sang; Kim, Kyoung; Moon, Nam
Abstract Background Postoperative adhesion is one of the major complications of strabismus surgery and result in motility dysfunction that brings unpredictable surgical outcomes. However, there was no definitely accepted treatment method to prevent postoperative adhesion. Methods A prospective, randomized, controlled experimental animal study was performed. Both eyes of each of 14 New Zealand White rabbits underwent superior rectus muscle recession. After the surgical procedure, the subjects were divided randomly into two groups; 0.5 % tranilast ophthalmic solutions and fluoroquinolone antibiotic eye drops were administered to the group tranilast (N = 14), while the group control (N = 14) received fluoroquinolone eye drops only. Five weeks after surgery, we evaluated gross adhesions with a numeric score (0 to 4). In addition, histopathologic examination with hematoxylin & eosin staining, Masson's-trichrome staining, and anti-transforming growth factor beta 1 (TGF-β1) immuno-histochemical staining were done. Results The group tranilast showed significantly less gross adhesion and inflammation than the group control (P = 0.01 andP < 0.001, respectively). Masson's-trichrome staining revealed that post-operative collagen deposition was more prominent in the group control than the group tranilast (P < 0.001). Moreover, remarkable TGF-β1 expression was observed in areas with excessive collagen deposition. Conclusions Instillation of 0.5 % tranilast ophthalmic solution is a simple and effective method for preventing post-operative adhesion after strabismus surgery.